Separation of Human Fibrinogen and Plasminogen by means of Gel Filtration - Berg, Walter; Korsan-Bengtsen, Kristoffer (Thrombosis and Haemostasis, 1963)
A simple method for removing contaminating plasminogen from fibrinogen is described. The method is based on gel filtration with Sephadex G-200.When purified fibrinogen was clotted in the presence of urokinase, no lysis was observed during an observation period of 4 weeks.